Lectora Inspire: Boosting environmental awareness with chicken bone cracker e-module - Melly Ismiyaturrohimah; Mustika Nuramalia Handayani; Gilang Garnadi Suryadi (Curricula: Journal of Curriculum Development, 2024)
Green skills are skills needed by students to support sustainable development goals. Environmental awareness and innovation skills, which are parts of green skills, have become essential competencies for participants of the Agribusiness in Agricultural Product Processing (APHP). The enhancement of environmental awareness and innovation skills can be achieved through the learning process using instructional media. The instructional media developed in this study is an e-module based on Lectora Inspire. This research aims to determine the suitability of the e-module for chicken bone cracker processing based on Lectora Inspire, to assess the environmental awareness and innovation skills of the learners. The development of this e-module follows the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation) and employs a pre-experimental design method with a one-group pretest-posttest design during its implementation. The research findings indicate that the e-module is considered "highly suitable" for use, as validated by subject matter experts, language experts, media experts, and learner responses. The results show that the learners' environmental awareness, as measured by average scores, has increased from the "low" to the "high" category using the e-module. Similarly, the learners' innovation skills, as measured by average scores, have improved from the "high" to the "very high" category.   Abstrak Green skills merupakan keterampilan yang dibutuhkan oleh peserta didik untuk mendukung tujuan pembangunan berkelanjutan. Environmental awareness dan innovatiion skill yang merupakan bagian dari green skills menjadi salah satu skill yang harus dimiliki oleh peserta didik APHP. Peningkatan environmental awareness dan innovatiion skill dapat dilakukan melalui proses pembelajaran dengan bantuan media pembelajaran. Media pembelajaran yang dikembangkan pada penelitian ini adalah e-modul berbasis Lectora Inspire. Tujuan penelitian ini adalah untuk mengetahui kelayakan e-modul pengolahan kerupuk tulang ayam berbasis Lectora Inspire, mengetahui environmental awareness dan innovation skill peserta didik. Pengembangan e-modul ini menggunakan model ADDIE (Analyze, Design, Development, Implementation, dan Evaluation) dan menggunakan metode pre-eksperimental design dengan rancangan one group pretest-posttest design pada penerapannya. Hasil penelitian menunjukkan bahwa e-modul dinyatakan “sangat layak” digunakan berdasarkan hasil validasi ahli materi, ahli bahasa, ahli media, serta respon peserta didik. Hasil environmental awareness peserta didik dengan e-modul mengalami peningkatan “sedang” berdasarkan uji n-gain dan hasil innovation skill peserta didik mengalami peningkatan “tinggi” berdasarkan uji n-gain.  Kata Kunci: e-module; kerupuk tulang ayam; kesadaran lingkungan; lectora inspire